INCREASING THE EFFICIENCY OF DOMESTIC TOURISM ACTIVITIES THROUGH DEVELOPING TRANSPORT INFRASTRUCTURE: MENINGKATKAN EFISIENSI KEGIATAN PARIWISATA DOMESTIK MELALUI PENGEMBANGAN INFRASTRUKTUR TRANSPORTASI - Maksudjon, Turopov (Academia Open, 2025)
Background: Domestic tourism has emerged as a strategic lever for economic and socio-cultural development in many nations. Specific Background: In Uzbekistan, tourism policy has increasingly emphasized enhancing internal mobility and regional connectivity. Knowledge Gap: However, despite a rich cultural and natural heritage, limitations in transport infrastructure have hindered the efficient utilization of domestic tourism potential. Aim: This study aims to examine the role of transport infrastructure development—airports, railways, public transport, and digital mobility solutions—in enhancing domestic tourism efficiency between 2020 and 2024. Results: Statistical analysis indicates that infrastructural investments, such as the modernization of Samarkand and Tashkent airports and the introduction of high-speed trains and metro systems, contributed to a substantial rise in domestic tourist flows (from 20.1 million in 2022 to 22.7 million in 2024). Novelty: The study introduces a holistic framework linking transport modernization with territorial tourism development, integrating infrastructural, economic, and digital dimensions. Implications: The findings underscore that without inclusive, modern, and strategically aligned transport systems, domestic tourism cannot realize its full economic and social potential-highlighting the need for equitable regional planning, digitization, and public-private partnership initiatives. Highlights: Strategic Role of Transport Efficient, modern, and inclusive transport infrastructure is essential for enhancing access to tourist destinations and increasing tourist satisfaction. Positive Impact of Reforms (2020–2024) Major upgrades like Samarkand and Tashkent airport modernization, introduction of high-speed trains, and metro expansion have boosted domestic tourism flow significantly. Remaining Challenges & Solutions Issues such as unequal regional access, underdeveloped rural transport, and lack of digital platforms persist; recommendations include digitalization, private sector partnerships, and promotion of eco-transport solutions. Keywords: Transport Infrastructure, Domestic Tourism, Uzbekistan, Public Transport, Infrastructure Reform